Biofluid markers of Equine neurological disorders reviewed from Human perspectives - Mayaki, Abubakar Musa; Abdul Razak, Intan Shameha; Mohd Adzahan, Noraniza; Mazlan, Mazlina; Abdullah, Rasedee (Elsevier, 2020)
Neurological disorders (NDs) are often fatal to horses. Thus, symptoms of equine NDs commonly indicate euthanasia. Current diagnostic approaches for equine NDs is based on clinical signs, differential diagnoses, analysis of cerebrospinal fluid (CSF), assessment of histopathological lesions, and imaging. However, advances in biofluid biomarkers in the diagnosis of human neurological diseases can potentially be applied to equine NDs. In this review, we described the established human blood and CSF neurobiomarkers that could potentially be used to diagnose equine NDs.